2013
DOI: 10.4141/cjas2013-020
|View full text |Cite
|
Sign up to set email alerts
|

Energy concentration and phosphorus digestibility in canola, cottonseed, and sunflower products fed to growing pigs

Abstract: Rodríguez, D. A., Sulabo, R. C., González-Vega, J. C. and Stein, H. H. 2013. Energy concentration and phosphorus digestibility in canola, cottonseed, and sunflower products fed to growing pigs. Can. J. Anim. Sci. 93: 493–503. Many protein sources are available to the swine feed industry, but accurate data for the energy concentration and the standardized total tract digestibility (STTD) of P in these ingredients are lacking. Therefore, two experiments were conducted to determine the concentration of digestible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
22
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 34 publications
13
22
5
1
Order By: Relevance
“…The ATTP of P without phytase in our study were higher than some of the published values for ATTD of P without phytase and such values were in between 27% and 33% (Wu et al 2008;Akinmusire and Adeola 2009;NRC 2012). However, current values for ATTD of P were lower than a study reported where the ATTD of P (%) were 52.2 and 68.9 without and with phytase, respectively (Rodríguez et al 2013). The reason behind the variability in P digestibility observed among canola seed and CM is due to the percentage of P that is bound to phytate where CM had higher digestibility than canola seed (Selle and Ravindran 2008;Rodríguez et al 2013).…”
Section: Landero Et Al (2012) Using Expeller Pressed CM (Epcm)contrasting
confidence: 48%
See 2 more Smart Citations
“…The ATTP of P without phytase in our study were higher than some of the published values for ATTD of P without phytase and such values were in between 27% and 33% (Wu et al 2008;Akinmusire and Adeola 2009;NRC 2012). However, current values for ATTD of P were lower than a study reported where the ATTD of P (%) were 52.2 and 68.9 without and with phytase, respectively (Rodríguez et al 2013). The reason behind the variability in P digestibility observed among canola seed and CM is due to the percentage of P that is bound to phytate where CM had higher digestibility than canola seed (Selle and Ravindran 2008;Rodríguez et al 2013).…”
Section: Landero Et Al (2012) Using Expeller Pressed CM (Epcm)contrasting
confidence: 48%
“…However, current values for ATTD of P were lower than a study reported where the ATTD of P (%) were 52.2 and 68.9 without and with phytase, respectively (Rodríguez et al 2013). The reason behind the variability in P digestibility observed among canola seed and CM is due to the percentage of P that is bound to phytate where CM had higher digestibility than canola seed (Selle and Ravindran 2008;Rodríguez et al 2013). The minimum ATTD of P in CM in the present experiment (39.76% for BNB) was closer to the percentage of nonphytate P (37%) in the BNB.…”
Section: Landero Et Al (2012) Using Expeller Pressed CM (Epcm)contrasting
confidence: 47%
See 1 more Smart Citation
“…The levels of CTTAD and CTTSD of P in CAM in the present study are almost two times greater than those reported by others (Fan & Sauer, 2002;Akinmusire & Adeola, 2009;NRC, 2012;Rodríguez et al, 2013). However, availability of P in CAM is lower than that of SBM (NRC, 2012;Rodríguez et al, 2013).…”
Section: Discussioncontrasting
confidence: 73%
“…However, availability of P in CAM is lower than that of SBM (NRC, 2012;Rodríguez et al, 2013). The reason for this might stem from the high level of phytate in CAM compared to SBM (NRC, 2012;Rodríguez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%